Gold Pawn Marketing Strategy to Increase the Number of Customers at Bank Syariah Indonesia KCP Rungkut 1 - Intan Permatasari; Rifa’atul Maftuhah; Fatkur Huda (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze the marketing strategy of the gold pawning product (rahn) at BSI KCP Rungkut 1 and its impact on the increase in the number of customers. Using a qualitative approach with a case study method, data were collected through interviews with internal bank representatives. The research findings indicate that the marketing strategies implemented encompass the 7Ps of marketing: a sharia-based product, competitive pricing without interest, active promotion through social media and direct visits to markets (